Furyl-substituted mixed phosphonium-iodonium ylides in the synthesis of annelated P-containing heterocyclic compounds - Matveeva, Elena D.; Vinogradov, Dmitrii S.; Podrugina, Tatyana A.; Nekipelova, Tatiana D.; Mironov, Andrey V.; Gleiter, Rolf; Zefirov, Nikolay S. (European journal of organic chemistry, 2015)
Abstract Photochemical reactions between stabilized furyl-substituted phosphonium?iodonium ylides and terminal acetylenes led to the formation of new P-containing heterocyclic compounds. For the heterocyclization of 2-furyl-substituted ylides, we observed an unprecedented electrophilic ipso attack onto the α position of the furan ring in a carbocationic intermediate, leading ? via a spiro intermediate ? to the rearranged product with a 2,3-shift in the furan ring.